6x-x+1=4x

Simple and best practice solution for 6x-x+1=4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-x+1=4x equation:



6x-x+1=4x
We move all terms to the left:
6x-x+1-(4x)=0
We add all the numbers together, and all the variables
x+1=0
We move all terms containing x to the left, all other terms to the right
x=-1

See similar equations:

| 4x+7.8-0.5x=1.2+8.49 | | 5(x-2)+2(1+3x=7x+12 | | x=5/x | | x+11=-5* | | x+6=5x-13 | | 6+10=8x12 | | 2(x+1)-3(2x-4)=-3(-x+1) | | 21=–5t–19 | | (4^a×2^a)=64 | | –45=4d+d | | 5(3w+5)/2=-2 | | -(3-x)=5x+2 | | 32*8/2=x | | 6a+12=54 | | (-4)-2=(-8k)+5= | | 2(x-2)=3(5-2x) | | 2(3a+1)=3(a-1) | | -9p+12+6p=-123 | | 4x-4-2x=-3x-9+2 | | -x^2+13x–42=9 | | (11/5)x+2=0 | | 13-5x=7x+73 | | 6m=4m-60 | | 10y-3y=64 | | 7x-5=7+x-9x+3 | | 16-2x=12-2x | | 0,2(x-3)-0.4(7-x)=-4.6 | | x-25=2x-65 | | 2x+10-2(6x-3)=5-12x+2(x-1) | | 3-x/3=2-x/4 | | x-1/8+1/5x-4/5=8/5x-1.2x+10-2(6x-3)=5-12x+2(x-1) | | x+(5+2x+)=17 |

Equations solver categories